MENATA MATERI DAN PENGALAMAN BELAJAR MAHASISWA PADA MATA KULIAH RESEARCH METHODOLOGY DENGAN STRATEGI ICARE - Sri Minda Murni (BAHAS, 2021)
Abstract  Review on the drafts of student research proposal shows low level competence as well as enthusiasm in producing innovative products. Students tend to copy-paste from previous theses rather than producing original product using one of the various method introduced in the Research Methodology subject. This article is aimed at designing more systematic materials and learning experiences for the students. The strategy chosen is ICARE (Introduction, Connection, Application, reflection, Extension).The result shows more focused and systematic material and learning experiences. It is expected that students will have more self-confidence in writing their research proposal without copy-pasting from the available these after using this new design.Keywords: Research method – ICARE - theses  AbstrakHasil review  atas rancangan proposal  skripsi yang dikirimkan mahasiswa menunjukkan kopetensi dan antusiasme yang rendah dalam menghasilakan proposal yang inovatif.  Mahasiswa cenderung meng-copy paste dari skripsi yang sudah ada dibanding menulis karya original yang menggunakan berbagai metode penelitian yang diperkenalkan pada matakuliah Research Methodology. Artikel ini bertujuan untuk merancang materi dan pengalaman belajar yang lebih sistematis bagi mahasiswa.  Strategi pengembangan yang dipilih adalah  ICARE (Introduction, Connection, Application, reflection, Extension). Hasil pengembangan menunjukkan rancangan materi dan pengalaman belajar yang lebih fokus dan sistematis. Harapanya mahasiswa lebih percaya diri dalam menulis proposal penelitian tanpa meng-copy paste skripsi-skripsi sebelumnya setelah menerima dan mengalami rancangan ini. Kata kunci: Research Method – ICARE – skripsi.